Shaper-assisted ultraviolet cross correlator - Möhring, Jens Markus; Buckup, Tiago; Motzkus, Marcus (Optics letters, 2010)
We successfully demonstrate the characterization of phase- and amplitude-modulated broadband UV pulses with a shaper-assisted cross-correlation setup. A two-dimensional pulse modulator, operated in the diffractive shaping mode, is used to generate an inherently temporally overlapped reference beam. To greatly improve the usability of this method, we combined this setup with a split-mirror UV autocorrelator based on a solar-blind photomultiplier tube as sensitive nonlinearity. This allows sensitive characterization of the Fourier-limited pulses down to a few picojoules, as well as complex-shaped ultrashort UV pulses, typically occurring in coherent control experiments.